Параметры изоляции распределительных сетей: контроль и управление - Шкрабец, Федор Павлович; Цыпленков, Дмитрий Владимирович; Кириченко, Марина Сергеевна; Ковалев, Александр Иванович (НТУ "ХПИ", 2010)
В статье изложены принципы косвенного дискретного контроля параметров изоляции на основе искусственного смещения нейтрали и непрерывного селективного контроля на основе наложения би-частотных оперативных сигналов в распределительных сетях напряжением 6-10 кВ. Указаны основные пути управления активным, реактивным сопротивлениями и добротностью изоляции сетей в аварийном режиме.

Principles of indirect discrete monitoring of insulation parameters are expounded on the basis of artificial displacement of the neutral and continuous selective control based on bifrequency operative signals overlapping in distributive mains of 6-10 kV. The basic ways of control of active, reactive resistances and insulation good quality of the mains under emergency conditions are shown.
Insulation parameters of distribution mains: monitoring and control
Keywords: изоляция электрических сетей; значения аварийных токов; однофазные замыкания; заземление нейтрали; insulation parameters monitoring; operative signal; displacement of neutral